2022
DOI: 10.1002/ccr3.6123
|View full text |Cite
|
Sign up to set email alerts
|

Autologous blood pleurodesis for surgical pneumothorax and outcome with multimodal cancer treatment in a dog with primary pulmonary mast cell tumor

Abstract: A dog underwent lung lobectomy for removal of a mass. Histopathology was consistent with narrow resection of a mast cell tumor. Postoperative pneumothorax was successfully treated using autologous blood pleurodesis. Progression of disease despite adjunctive treatment with several chemotherapetutic agents and radiation therapy resulted in euthanasia approximately 4 months postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…6 , 7 In dogs and cats, BPP has been a documented cost-effective and successful pleurodesis method in situations where surgery has been declined or where persistent pneumothorax occurs. 8 15 …”
Section: Discussionmentioning
confidence: 99%
“…6 , 7 In dogs and cats, BPP has been a documented cost-effective and successful pleurodesis method in situations where surgery has been declined or where persistent pneumothorax occurs. 8 15 …”
Section: Discussionmentioning
confidence: 99%
“…Shinsako et al. described the use of ABPP for treatment of pneumothorax in a dog with a primary pulmonary mast cell tumour 20 . However, that pneumothorax developed 12 hours post‐operatively following a lung lobectomy for mass removal of the primary tumour, and was believed to be secondary to lung lobectomy, not the neoplasm itself 20 .…”
Section: Discussionmentioning
confidence: 99%
“…20 However, that pneumothorax developed 12 hours post-operatively following a lung lobectomy for mass removal of the primary tumour, and was believed to be secondary to lung lobectomy, not the neoplasm itself. 20 To the authors' knowledge, this is the first reported case of pneumothorax suspected to be secondary to metastatic disease in a dog, and the only published report of the use of ABPP to palliate it. Although this patient was ultimately euthanased, this procedure increased both its quantity and quality of life following development of the pneumothorax.…”
Section: Au T H O R C O N T R I B U T I O N S Tat E M E N Tmentioning
confidence: 99%
See 1 more Smart Citation